Is indirect discrimination unjust? - Lippert-Rasmussen, Kasper (Politica, 2023)
Many believe that indirect discrimination is unjust as such, because, by definition, it involves the imposition of disproportionate disadvantages on the group of discriminatees. In this article I ask two questions: 1) What does it take to disadvantage a group, and 2) which groups are relevant for the purpose of determining whether a given practice is indirectly discriminatory? I argue that it is difficult to answer these two questions in a way that aligns both with the way in which we normally think about indirect discrimination and the view that indirect discrimination necessarily clashes with the moral concerns that we normally think render indirect discrimination morally objectionable. In the last part of the article, I explain why the article’s negative main claim – that indirect discrimination is not unjust in itself – does not entail that we should refrain from reducing or prohibiting indirect discrimination.